2024
DOI: 10.1002/ece3.11339
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of the two genetic groups of Corbicula fluminea in a lotic–lentic system

Meixiang Jia,
Fei Cheng,
Jin Li
et al.

Abstract: Differences in local habitat conditions are often implicated as drivers for morphological and genetic divergence in natural populations. However, there are still relatively few studies regarding how divergent habitats influence patterns for morphotypes and genetic lineages in aquatic invertebrates. In this study, we explored the morphological patterns, genetic divergence, and distributions of a bivalve, Corbicula fluminea, in a lotic–lentic system. Sampling locations included lotic, ecotone, and lentic habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Consequently, the scientific consensus has leaned towards classifying Corbicula as a "complex of polymorphic species" [6]. However, this classification does not imply ecological equivalence among different forms; in fact, there are lineage disparities not only in morphology but also in microhabitat preferences [60,61], individual growth rates [62,63], reproductive event frequency, offspring release numbers [64], and physiological traits such as filtration [65] and metabolic rates [17]. The pronounced segregation of forms and haplotypes discovered across Argentina bolsters this notion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the scientific consensus has leaned towards classifying Corbicula as a "complex of polymorphic species" [6]. However, this classification does not imply ecological equivalence among different forms; in fact, there are lineage disparities not only in morphology but also in microhabitat preferences [60,61], individual growth rates [62,63], reproductive event frequency, offspring release numbers [64], and physiological traits such as filtration [65] and metabolic rates [17]. The pronounced segregation of forms and haplotypes discovered across Argentina bolsters this notion.…”
Section: Discussionmentioning
confidence: 99%
“…The pronounced segregation of forms and haplotypes discovered across Argentina bolsters this notion. It has been suggested that some of the variability in life-history traits may have a genetic basis [11,61], although phenotypic plasticity could also be a contributing factor, as observed in other freshwater invasive bivalves [16]. Further research is necessary to determine their relative significance, as well as to assess the potential adaptive advantages conferred by these differences in various environmental conditions, and their implications for distribution patterns.…”
Section: Discussionmentioning
confidence: 99%